2014
DOI: 10.1016/j.jaci.2013.12.935
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Drug Reactions (HDR) In Latin America. Similarities and Differences Between Children and Adults

Abstract: RATIONALE: HDR are frequent motives for consultation in Allergology services. Possible etiologic factors and clinical presentation differences between Latin American children and adults have not been described yet. METHODS: An observational cross sectional study using a modified ENDA questionnaire was implemented in 19 allergology units in 11 Latin-American countries, reporting patients presenting HDR in the last year before consultation. Causal relationship was categorized according to WHO-UMC Causality Categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the work by Doña et al [4], which includes the largest series of subjects suffering from HRs to drugs studied to date, the most frequently confirmed diagnosis was hypersensitivity to multiple NSAIDs (47.29%), followed by immediate reactions to beta-lactam (18.12%) and quinolone (6.8%) antibiotics. A recent multicenter study presented at the last meeting of the American Academy of Allergy, Asthma and Immunology including more than 700 cases from 11 countries showed that NSAIDs accounted for 55 and 60% of reactions in adults and children respectively, whereas beta-lactams were responsible for less than 20% of the reactions in both groups [5]. Moreover, recent works by Zambonino et al [6,7 ]showed that only 8% of patients with symptoms suggestive of beta-lactam hypersensitivy could be confirmed as such compared to 68% for NSAID-hypersensitive patients.…”
mentioning
confidence: 99%
“…In the work by Doña et al [4], which includes the largest series of subjects suffering from HRs to drugs studied to date, the most frequently confirmed diagnosis was hypersensitivity to multiple NSAIDs (47.29%), followed by immediate reactions to beta-lactam (18.12%) and quinolone (6.8%) antibiotics. A recent multicenter study presented at the last meeting of the American Academy of Allergy, Asthma and Immunology including more than 700 cases from 11 countries showed that NSAIDs accounted for 55 and 60% of reactions in adults and children respectively, whereas beta-lactams were responsible for less than 20% of the reactions in both groups [5]. Moreover, recent works by Zambonino et al [6,7 ]showed that only 8% of patients with symptoms suggestive of beta-lactam hypersensitivy could be confirmed as such compared to 68% for NSAID-hypersensitive patients.…”
mentioning
confidence: 99%